Survival trends in patients diagnosed with colon and rectal cancer in the nordic countries 1990–2016: The NORDCAN survival studies. (September 2022) - Lundberg, Frida E.; Birgisson, Helgi; Johannesen, Tom B.; Engholm, Gerda; Virtanen, Anni; Pettersson, David; Ólafsdóttir, Elínborg J.; Lambe, Mats; Lambert, Paul C.; Mørch, Lina S.; Johansson, Anna L.V.; Andersson, Therese M.-L.
Abstract: Background: Survival of patients with colon and rectal cancer has improved in all Nordic countries during the past decades. The aim of this study was to further assess survival trends in patients with colon and rectal cancer in the Nordic countries by age at diagnosis and to present additional survival measures. Methods: Data on colon and rectal cancer cases diagnosed in the Nordic countries between 1990 and 2016 were obtained from the NORDCAN database. Relative survival was estimated using flexible parametric models. Both age-standardized and age-specific measures for women and men were estimated from the models, as well as reference-adjusted crude probabilities of death and life-years lost. Results: The five-year age-standardized relative survival of colon and rectal cancer patients continued to improve for women and men in all Nordic countries, from around 50% in 1990 to about 70% at the end of the study period. In general, survival was similar across age and sex. The largest improvement was seen for Danish men and women with rectal cancer, from 41% to 69% and from 43% to 71%, respectively. The age-standardized and reference-adjusted five-year crude probability of death in colon cancer ranged from 30% to 36% across countries, and for rectal cancer from 20% to 33%. The average number of age-standardized and reference-adjusted life-years lost ranged between six and nine years. Conclusion: There were substantial improvements in colon and rectal cancer survival in all Nordic countries 1990–2016. Of special note is that the previously observed survival disadvantage in Denmark is no longer present. Highlights: Substantial improvements in survival seen for patients with colon and rectal cancer. Previously observed survival disadvantage in Denmark is no longer present. Improvements in survival seen in both women and men and across age. Age-standardized five-year relative survival around 70% at end of study period.